Total decay rates of B mesons at NNLO-QCD - Manuel Egner; Matteo Fael; Alexander Lenz; Maria Laura Piscopo; Aleksey V. Rusov; Kay Schönwald; Matthias Steinhauser (Journal of High Energy Physics)
Abstract We update the Standard Model (SM) predictions for the lifetimes of the B +, B d and B s mesons within the heavy quark expansion (HQE), including the recently determined NNLO-QCD corrections to non-leptonic decays of the free b-quark. In addition, we update the HQE predictions for the lifetime ratios τ (B +)/τ (B d ) and τ (B s )/τ (B d ), and provide new results for the semileptonic branching fractions of the three mesons entirely within the HQE. We obtain a considerable improvement of the theoretical uncertainties, mostly due to the reduction of the renormalisation scale dependence when going from LO to NNLO, and for all the observables considered, we find good agreement, within uncertainties, between the HQE predictions and the corresponding experimental data. Our results read, respectively, Γ(B +) = 0.587 − 0.035 + 0.025 $$ {0.587}_{-0.035}^{+0.025} $$ ps−1, Γ(B d ) = 0.636 − 0.037 + 0.028 $$ {0.636}_{-0.037}^{+0.028} $$ ps−1, Γ(B s ) = 0.628 − 0.035 + 0.027 $$ {0.628}_{-0.035}^{+0.027} $$ ps−1, for the total decay widths, τ (B +)/τ (B d ) = 1.081 − 0.016 + 0.014 $$ {1.081}_{-0.016}^{+0.014} $$ , τ (B s )/τ (B d ) = 1.013 − 0.007 + 0.007 $$ {1.013}_{-0.007}^{+0.007} $$ , for the lifetime ratios, and B sl B + $$ {\mathcal{B}}_{sl}\left(B^{+}\right) $$ = 11.46 − 0.32 + 0.47 % $$ \left({11.46}_{-0.32}^{+0.47}\right)% $$ , B sl B d $$ {\mathcal{B}}_{sl}\left(B_d\right) $$ = 10.57 − 0.27 + 0.47 % $$ \left({10.57}_{-0.27}^{+0.47}\right)% $$ , B sl B s $$ {\mathcal{B}}_{sl}\left(B_s\right) $$ = 10.52 − 0.29 + 0.50 % $$ \left({10.52}_{-0.29}^{+0.50}\right)% $$ , for the semileptonic branching ratios. Finally, we also provide an outlook for further improvements of the HQE determinations of the B-meson decay widths and of their ratios.